Punctuation and the Sanskrit Language - Jatindra Mohan Mishra (JOURNAL OF INDIAN EDUCATION, 2025)
Today, almost all the written languages in the world use punctuation marks. Origin of these can be traced as long as 2500 years ago in Europe. But the standardisation of them can be attributed to the evolution of print technology. Now it looks like punctuation is an essential part of a written expression in any language. In this globalised world, English being the international language is imitated for its punctuation marks by almost all the languages of the world, including Sanskrit.